Biological coloration of flax fabrics with flavonoids using laccase from trametes hirsuta - Kim, Suyeon (2008)
Biological environmentally friendly concepts are emerging to replace chemical treatments of fabrics. In this work, a new process for the coloration of flax fabrics via enzymatic oxidation of natural flavonoids (morin, quercetin) has been developed. Laccase from Trametes hirsuta is able to react with flavonoids and polymerize them, resulting in a strongly colored polymeric solution which can be applied to the coloration of flax fabrics. Two methods were investigated: (i) the simultaneous enzymatic polymerization and coloration of fabrics and (ii) the polymerization of flavonoids with laccase, followed by a further coloration of the flax fabrics. Factors such as temperature, reaction time, presence of NaCl or the use of bleached or unbleached fabrics were evaluated in order to increase the color of the fabrics and the color fastness. The increase of temperature, the presence of salt and the use of unbleached fabrics allowed the final color to be improved. Colorized flax fabrics with oxidized quercetin solution showed a color fixation two times higher than the fabrics colorized with oxidized morin. Finally, the polymerization of flavonoids and their binding to fibers were verified using Fourier transform infrared spectroscopy (FT-IR). The results confirmed this environmentally friendly process as useful for the coloration of flax fabrics. A similar technique could also be extended to the treatment of other types of fabrics in textile processes.